2021
DOI: 10.1001/jamanetworkopen.2021.4123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Factors, Treatment Patterns, and Overall Survival Associated With Rare Triple-Negative Breast Carcinomas in the US

Abstract: IMPORTANCE Triple-negative breast cancers are known collectively to demonstrate a more aggressive clinical course and earlier recurrence than cancers of other histological subtypes.However, the literature on rare triple-negative breast cancers and the association of histological type with survival and risk of metastasis is sparse.OBJECTIVE To present the clinical and demographic characteristics, treatment patterns, and overall survival (OS) for histologically rare (<10% of breast cancers) triple-negative breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…The myoepithelial/abluminal cells express p63, smooth muscle actin and basal CKs: CK5/6, CK14, CK17. CAdCC generally displays a triple-negative immunophenotype, although ER-positive cases also occur ( Supplementary Table S2 ) [ 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. CAdCC frequently expresses EGFR, an immunohistochemical marker of the “basal-like” phenotype, without gene amplification [ 69 ].…”
Section: Classic Adenoid Cystic Carcinoma (Cadcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The myoepithelial/abluminal cells express p63, smooth muscle actin and basal CKs: CK5/6, CK14, CK17. CAdCC generally displays a triple-negative immunophenotype, although ER-positive cases also occur ( Supplementary Table S2 ) [ 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. CAdCC frequently expresses EGFR, an immunohistochemical marker of the “basal-like” phenotype, without gene amplification [ 69 ].…”
Section: Classic Adenoid Cystic Carcinoma (Cadcc)mentioning
confidence: 99%
“…Taking account of the publications to date, the median age of patients with AdCC ranged from 58 to 66 years. Data on the ethnical differences are limited, but larger registry-based series suggest that approximately 85% of patients diagnosed in the USA were whites [ 46 , 48 , 50 , 52 , 53 ]. The majority of patients presented with a palpable mass (85.7%) and underwent lumpectomy, breast-conserving surgery (BCS) or mastectomy.…”
Section: Classic Adenoid Cystic Carcinoma (Cadcc)mentioning
confidence: 99%
“…One patient from our case series who presented with lung metastasis was received palliative chemotherapy (4 cycles of FEC regimen, and 2 cycles of docetaxel) and also received second line chemotherapy paclitaxel, experienced no reduction in tumor size along with worsening lung metastasis. Although evidence shown little benefit of systemic therapy in metastatic disease of MBC, it was also demonstrated that those who did not received chemotherapy or undergo any surgical treatment over the site of primary tumor, was associated with decreased survival outcome [ 16 ]. Corso et al found that patients who received CMF/CMF like regimen showed better prognosis and improved overall survival [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al revealed that the 5 year overall survival rate of MBC patients was shorter compared to that of invasive ductal carcinoma patient group and triple negative subtype of invasive ductal carcinoma patients (78.7% vs 93% vs 90.6%) [ 3 ]. Elimimian et al demonstrated inferior prognosis of MBC patient group compared to 2 other special type of breast carcinoma, which is adenoid cystic carcinoma and medullary carcinoma (5 year overall survival rate: 63.1% cs 88.4% vs 91.7%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the rare breast ACC cases without the MYB-NFIB gene fusion, additional genomic alterations have been detected, including MYB gene amplification and MYBL1 gene rearrangement [ 6 ]. Although the immunohistochemical phenotype of most ACC of the breast is triple-negative, the prognosis is better than that of other triple-negative breast cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%